INTER-CONNECTEDNESS BETWEEN DEVELOPED AND VISEGRAD STOCK MARKETS DURING COVID-19 PANDEMIC AND RUSSIA-UKRAINE WAR - Pruchnicka-Grabias, Izabela; Żebrowska-Suchodolska, Dorota (Torun International Studies, 2024)
Purpose: The study checks relations between different developed and Visegrad stock markets and mainly concentrates on the analysis of the American market influence (reflected by S&P500) on other stock markets. It examines the influence of crisis situations such as Covid-19 pandemic and Russia-Ukraine war on the strength of the linkage between markets. Methodology/approach: The study of changes in the dependence of stock market indices over 2018 – 2023 is conducted using rolling windows for the Pearson correlation coefficient. The similarity strength of indices is indicated using the DTW measure. The influence of the S&P500 index on other stock indices is examined by the Granger causality. Findings: We show that both the Covid-19 pandemic and the war increased the linkage between stock markets, although for the latter this rule refers only to markets that are geographically close to the conflict zone. The research also shows that the American stock exchanges are the most strongly interconnected. Another important notice is that crises decrease the similarity of shapes between stock exchanges represented by market indices. Moreover, greater similarity between stock exchanges leads to lower volatility in correlations over time. Originality/value: The paper adds value in three aspects. The first one is that it examines changes in relations between indices, both in their correlations and their similarities strength during Covid-19 pandemic and Russia-Ukraine war – recent crisis situations. Contrary to the previous literature which is rather concentrated on the Covid-19 pandemic and its influence on stock markets, we show that such events that are not global also influence relations between stock markets close to the conflict zone. The second one is combining in one paper connections between both different indices from developed countries and Visegrad countries. The third one is using DTW method rarely used for financial time series analysis to examine shapes similarity between S&P500 index and so many stock markets, both from developed and Visegrad countries in one paper.